Characterization of the microbial communities along the gastrointestinal tract of sheep by 454 pyrosequencing analysis - Jin Wang; Huan Fan; Ye Han; Jinzhao Zhao; Zhijiang Zhou (Asian-Australasian Journal of Animal Sciences, 2017)
Objective The gastrointestinal tract of sheep contain complex microbial communities that influence numerous aspects of the sheep’s health and development. The objective of this study was to analyze the composition and diversity of the microbiota in the gastrointestinal tract sections (rumen, reticulum, omasum, abomasum, duodenum, jejunum, ileum, cecum, colon, and rectum) of sheep. Methods This analysis was performed by 454 pyrosequencing using the V3-V6 region of the 16S rRNA genes. Samples were collected from five healthy, small tailed Han sheep aged 10 months, obtained at market. The bacterial composition of sheep gastrointestinal microbiota was investigated at the phylum, class, order, family, genus, and species levels. Results The dominant bacterial phyla in the entire gastrointestinal sections were Firmicutes, Bacteroidetes, and Proteobacteria. In the stomach, the three most dominant genera in the sheep were Prevotella, unclassified Lachnospiraceae, and Butyrivibrio. In the small intestine, the three most dominant genera in the sheep were Escherichia, unclassified Lachnospiraceae, and Ruminococcus. In the large intestine, the three most dominant genera in the sheep were Ruminococcus, unclassified Ruminococcaceae, and Prevotella. R. flavefaciens, B. fibrisolvens, and S. ruminantium were three most dominant species in the sheep gastrointestinal tract. Principal Coordinates Analysis showed that the microbial communities from each gastrointestinal section could be separated into three groups according to similarity of community composition: stomach (rumen, reticulum, omasum, and abomasum), small intestine (duodenum, jejunum, and ileum), and large intestine (cecum, colon, and rectum). Conclusion This is the first study to characterize the entire gastrointestinal microbiota in sheep by use of 16S rRNA gene amplicon pyrosequencing, expanding our knowledge of the gastrointestinal bacterial community of sheep.